STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR DALAM PENGELOLAAN ADMINISTRASI KEPENDUDUKAN TAHUN 2017-2018 - Irawan, Andre; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Law Number 23 of 2006 concerning Population Administration, this Population administration contains the regulation and formation of a system that reflects reforms in the field of Population Administration. But in reality, the implementation of population administration management, especially in the E-KTP sector, has not yet been realized based on the management strategy stated in the Strategic Plan of the Population and Civil Registration Service of Kampar Regency for 2017-2018. The formulation of the problem in this study is how the Strategy of the Department of Population and Civil Registration of Kampar Regency in Population Administration Management for 2017-2018? .This study aims to (1) describe the strategy of the Kampar Regency Population and Civil Registration Service in managing the 2017-2018 population administration, (2) describe the factors that hinder the strategy of the Kampar Regency Population and Civil Registration Service in managing population administration for 2017-2018. This research is a descriptive study with a qualitative approach. The location of this research was conducted at the Department of Population and Civil Registration of Kampar Regency. Data collection techniques used are through interviews and documentation. The data analysis technique used is an interactive analysis model.The results of the study concluded that based on the observations and analysis of researchers on the realization of the implementation of administrative management strategies, especially in the field of E-KTP by the Department of Population and Civil Registration of Kampar Regency 2017-2018, it is still not optimal based on the service strategy stated in the Strategic Plan. The efforts made by the Population and Civil Registration of Kampar Regency are influenced by internal factors and external factors. Internal factors are inadequate human resources, as well as limited facilities and infrastructure. While external factors are low participation and understanding of the community as service users in carrying out administrative services, especially the management of E-KTP at the Department of Population and Civil Registration of Kampar Regency.Keywords: Service Strategy, E-KTP Administration Management, Inhibiting FactorsÂ